Venus Flytrap (Dionaea muscipula Solander ex Ellis) Contains Powerful Compounds that Prevent and Cure Cancer - Gaascht, Francois; Dicato, Mario; Diederich, Marc (Frontiers in Oncology, 2013)
Chemoprevention uses natural or synthetic molecules without toxic effects to prevent and/or block emergence and development of diseases including cancer. Many of these natural molecules modulate mitogenic signals involved in cell survival, apoptosis, cell cycle regulation, angiogenesis or on processes involved in the development of metastases occur naturally, especially in fruits and vegetables bur also in non-comestible plants. Carnivorous plants including the Venus flytrap (Dionaea muscipula Solander ex Ellis) are much less investigated, but appear to contain a wealth of potent bioactive secondary metabolites. Aim of this review is to give insight into molecular mechanisms triggered by compounds isolated from these interesting plants with either therapeutic or chemopreventive potential.